Evaluation of brain damage resulting from penetrating and non-penetrating stunning in Nelore Cattle using pneumatically powered captive bolt guns - Octavio Oliveira, Steffan Edward [UNESP]; Dalla Costa, Filipe Antonio [UNESP]; Gibson, Troy John; Dalla Costa, Osmar Antonio; Coldebella, Arlei; Gregory, Neville George (Elsevier B.V., 2018)
Brain damage resulting from penetrating and non-penetrating stunning of Nelore cattle using pneumatically powered captive bolt guns was evaluated. Heads were shot using penetrating captive bolt gun with 160psi (P1; n = 10), 175psi (P2; n = 10), 190psi (P3; n = 12), and non-penetrating operating with 220psi (NP; n = 10). Skin and bone thickness, bolt penetration angle, bolt penetration depth, haemorrhage over the cerebral hemispheres and laceration were assessed. Only P1 had shots that failed to perforate the skull (n = 2; 20%). Bolt penetration depth and haemorrhage over the right cerebral hemisphere was significantly (P <= 0.05) greater for P3. Subarachnoid haemorrhage over the frontal, parietal and occipital lobes was higher for NP. Lacerations were observed only for penetrating gun in the cortical region of frontal and parietal lobes. Subarachnoid haemorrhage surrounding the brainstem and laceration in the midbrain and pons was only found for P3. Thus, penetrating captive bolt gun operating with 190psi is more effective to achieve unconsciousness.
Keywords: Brain pathology; Bulls; Brainsteam; Pneumatic captive bolt stunning; Haemorrhage; Slaughter